Solid electrolyte and method for producing the same

The development of a solid electrolyte with specific X-ray diffraction peak characteristics through mechanical alloying and calcination addresses the challenge of low lithium ion conductivity in existing materials, achieving superior conductivity and crystallinity.

JP2025043171APending Publication Date: 2025-03-28MITSUI MINING & SMELTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150536
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing solid electrolytes have lower lithium ion conductivity compared to desired levels, necessitating the development of materials with enhanced conductivity.

Method used

A solid electrolyte with specific X-ray diffraction peak characteristics, including peaks A, C, and optionally D, E, and F, is produced using a method involving mechanical alloying and calcination of LiX and YCl3 powders under an inert gas atmosphere.

Benefits of technology

The resulting solid electrolyte exhibits significantly higher lithium ion conductivity than prior art materials, with improved crystallinity and disorder at the X element site contributing to enhanced conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043171000001_ABST
    Figure 2025043171000001_ABST
Patent Text Reader

Abstract

To provide a solid electrolyte having lithium ion conductivity higher than that of a solid electrolyte of a prior art.SOLUTION: A solid electrolyte has such a peak A that a value of a diffraction angle 2θ is within a range of 13.4° or more and 14.4° or less, in an X-ray diffraction pattern using Cu-Kα1 as a radiation source, and has such a peak C that the value is within a range of 30.7° or more and 33.7° or less, wherein when a total sum of half-value widths of the peak A is represented by WA, and a total sum of half-value widths of the peak C is represented by WC, a value of WC / WA is 2.0 or more. Preferably, the solid electrolyte has such a peak D that the value of the diffraction angle 2θ is within a range of 43.8° or more and 48.8° or less, and when a total sum of half-value widths of the peak D is represented by WD, a value of WD / WA is 3.7 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte and a method for producing the same. [Background technology]

[0002] In recent years, secondary batteries have been attracting attention as an effort to prevent global warming by reducing CO2 emissions. Among them, solid-state batteries using a solid electrolyte instead of an electrolytic solution have been attracting attention. As one of the solid electrolytes having lithium ion conductivity, one containing lithium (Li), yttrium (Y) and halogen (X) elements and having a composition formula represented by Li3YX6 is known. For example, Patent Document 1 discloses a solid electrolyte obtained by intensively mixing powders of lithium bromide, lithium iodide, yttrium bromide and yttrium iodide, and then sintering the mixture. Patent Document 2 discloses a solid electrolyte obtained by intensively mixing powders of lithium chloride, lithium bromide, lithium iodide, yttrium chloride, yttrium bromide, and yttrium iodide. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 135316 Brochure [Patent Document 2] International Publication No. 2019 / 135319 Brochure Summary of the Invention [Problem to be solved by the invention]

[0004] In the technical field, there is a demand for solid electrolytes having higher lithium ion conductivity than ever before. It is therefore an object of the present invention to provide a solid electrolyte having higher lithium ion conductivity than the solid electrolytes of the prior art mentioned above. [Means for solving the problem]

[0005] The present invention relates to an X-ray diffraction pattern using Cu-Kα1 as a radiation source. Peak A is in the range of diffraction angle 2θ values ​​of 13.4° or more and 14.4° or less, and peak C is in the range of 30.7° or more and 33.7° or less, The sum of the half-widths of peaks A is W A The sum of the half-widths of peaks C is W C Then, W C / W A The present invention provides a solid electrolyte having a value of 2.0 or more.

[0006] The present invention also provides a method for producing a fluorine-based ion-exchange membrane comprising the steps of: mixing LiX (X represents a halogen element, and the X element is at least one element selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I)) with YCl3 by mechanical alloying; and firing the treated product obtained by mixing in an inert gas atmosphere at a temperature equal to or higher than the melting point of LiX. Effect of the Invention

[0007] The present invention provides a solid electrolyte that has higher lithium ion conductivity than prior art solid electrolytes. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is an explanatory diagram showing the half-value width of an X-ray diffraction peak. [Diagram 2] FIG. 2 is an X-ray diffraction chart of the solid electrolytes obtained in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will now be described based on preferred embodiments with reference to the drawings. The solid electrolyte of the present invention is preferably a crystalline substance. The solid electrolyte of the present invention preferably exhibits a diffraction peak at a specific angle in a diffraction pattern obtained by subjecting the solid electrolyte to an X-ray diffraction method. A solid electrolyte exhibiting a diffraction peak at a specific angle exhibits higher lithium ion conductivity than solid electrolytes of the prior art.

[0010] In detail, the solid electrolyte of the present invention has a peak A in the X-ray diffraction pattern in the range of the diffraction angle 2θ of 13.4° or more and 14.4° or less. In order to further increase the lithium ion conductivity of the solid electrolyte, it is preferable that Peak A is observed at, for example, 13.6° or more, particularly 13.8° or more, and it is preferable that Peak A is observed at 14.2° or less, particularly 14.0° or less. The number of peaks A observed within the range of the diffraction angle 2θ may be one, or may be two or more. In obtaining the X-ray diffraction pattern, Cu-Kα1 is used as a radiation source. Hereinafter, in all cases where X-ray diffraction patterns are mentioned in this specification, Cu-Kα1 is used as the radiation source.

[0011] The solid electrolyte of the present invention preferably has Peak C in a range of diffraction angle 2θ of 30.7° or more and 33.7° or less. In order to further increase the lithium ion conductivity of the solid electrolyte, Peak C is preferably observed at, for example, 31.0° or more, particularly 31.5° or more, and is preferably observed at 33.5° or less, particularly 33.0° or less. The number of peaks C observed within the range of the diffraction angle 2θ may be one, or may be two or more.

[0012] The above-mentioned peaks A and C are also characterized by their broadness. In particular, the sum of the half-widths of peaks A and C is W A (°), and the sum of the half-widths of peaks C and C is W C (°), W C / W AIt is preferable that the value of W is 2.0 or more, in other words, that the peak C is broader than the peak A, in order to further increase the lithium ion conductivity of the solid electrolyte. C / W A The value of is, for example, more preferably 2.3 or more, and even more preferably 2.5 or more. C / W A The value may be, for example, 50 or less, 25 or less, or 10 or less.

[0013] When there are multiple peaks A, the half-width W A When calculating the half-width W, even if multiple peaks overlap, no peak separation is performed. For example, as shown in Figure 1, when two peaks I and II partially overlap, A is the half-width W of peak I I and the half-width W of peak II II The sum of A =W I +W II ) is defined as the half-width W of peak C. C , and the half-width W of peak D described later D The same applies to.

[0014] In addition to the above-mentioned peaks A and C, the solid electrolyte of the present invention preferably has a peak D in the range of a diffraction angle 2θ value of 43.8° or more and 48.8° or less. When the solid electrolyte has peak D, the lithium ion conductivity of the solid electrolyte can be further increased. From the viewpoint of further increasing the lithium ion conductivity of the solid electrolyte, it is preferable that peak D is observed at, for example, 44.5° or more, particularly 45.5° or more, and it is preferable that peak D is observed at 48.0° or less, particularly 47.0° or less. The number of peaks D observed within the range of the diffraction angle 2θ may be one, or may be two or more.

[0015] Like the above-mentioned peak C, it is preferable that the peak D is broader than the peak A in order to further increase the lithium ion conductivity of the solid electrolyte. D Then, W D / W A It is preferable that the value of W is 3.7 or more. D / W A The value of W is, for example, more preferably 3.8 or more, and even more preferably 4.0 or more. D / W A The value may be, for example, 50 or less, 25 or less, or 10 or less.

[0016] The solid electrolyte of the present invention may have other peaks in addition to the above-mentioned peaks A, C, and D. In order to further increase the lithium ion conductivity of the solid electrolyte, the solid electrolyte may have peak B in the range of 26.2° or more and 29.2° or less. In order to further increase the lithium ion conductivity of the solid electrolyte, peak B is preferably observed at, for example, 26.5° or more, particularly 27.0° or more, and is preferably observed at 28.5° or less, particularly 28.0° or less. The number of peaks B observed within the range of the diffraction angle 2θ may be one, or may be two or more.

[0017] The solid electrolyte of the present invention may have a peak E in the range of 53.3° or more and 56.6° or less in order to further increase the lithium ion conductivity of the solid electrolyte. In order to further increase the lithium ion conductivity of the solid electrolyte, the peak E is preferably observed at, for example, 53.5° or more, particularly preferably 54.0° or more, and is preferably observed at 56.0° or less, particularly preferably 55.5° or less. The number of peaks E observed within the range of the diffraction angle 2θ may be one, or may be two or more.

[0018] The solid electrolyte of the present invention may have a peak F in the range of 55.9° or more and 59.0° or less in order to further increase the lithium ion conductivity of the solid electrolyte. In order to further increase the lithium ion conductivity of the solid electrolyte, the peak F is preferably observed at, for example, 56.2° or more, particularly preferably 56.5° or more, and is preferably observed at 58.5° or less, particularly preferably 58.0° or less. The number of peaks F observed within the range of the diffraction angle 2θ may be one, or may be two or more.

[0019] It is preferable that the solid electrolyte of the present invention has all of the above-mentioned peaks A, B, C, D, E and F in terms of further improving lithium ion conductivity.

[0020] As described above, the solid electrolyte of the present invention is one in which a plurality of peaks including peak A are observed in the diffraction pattern measured by X-ray diffraction, and peak P having the highest peak intensity among the observed peaks is max The peak intensity I max Based on the intensity of peak A, I A It is preferable that the relative intensity of peak A is 25.0 or more in order to further increase the lithium ion conductivity of the solid electrolyte. A is the peak intensity I max It is more preferable that the relative intensity is, for example, 30.0 or more, and even more preferable that the relative intensity is 35.0 or more. Highest peak intensity I max From the viewpoint of further improving the lithium ion conductivity, it is preferable that the peak at which this is observed is peak B or peak C. In this specification, the intensity of a diffraction peak refers to the height of the diffraction peak (counts / sec), where the height of the diffraction peak is determined based on a linear scale. In this specification, the relative intensity of peak A is the peak intensity I max Intensity I of peak A when is set to 100 AThe same is true for the intensities of peaks B to F.

[0021] The solid electrolyte of the present invention is preferably composed of lithium (Li), yttrium (Y), and halogen (X) from the viewpoint of further improving lithium ion conductivity. In this case, the solid electrolyte of the present invention is preferably represented by the composition formula Li3YX6 from the viewpoint of further improving lithium ion conductivity. For the same reason, the solid electrolyte of the present invention is preferably a monoclinic crystal system.

[0022] From the viewpoint of further improving lithium ion conductivity, the X element is preferably one or more elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).

[0023] When the solid electrolyte of the present invention is composed of Li, Y and X elements, the inventors believe that the above-mentioned peak A is a peak that is not easily affected by the presence of X element. In contrast, the inventors believe that peaks B, C, D, E and F are peaks that are easily affected by the presence of X element. And, the inventors believe that when the degree of disorder at the site where the X element is located in the crystal of the solid electrolyte of the present invention increases, the activation energy for lithium ion conduction decreases and the lithium ion conductivity improves. The degree of disorder can be evaluated by the degree of broadness of the diffraction peak in the X-ray diffraction pattern, that is, the half-width. It is considered that the larger the half-width, the greater the degree of disorder and the better the lithium ion conductivity. Therefore, in the present invention, as described above, W C / W A The value of W D / W A This specifies the value of

[0024] In order to increase the degree of disorder at the site where the X element is located in the crystal of the solid electrolyte of the present invention, it is also preferable that the X element is two or more elements selected from the group consisting of F element, Cl element, Br element and I element. From the same viewpoint, it is also preferable that the X element is three or more elements selected from the group consisting of F element, Cl element, Br element and I element. The degree of disorder is greater when the solid electrolyte of the present invention contains three or more elements as the X element than when it contains two or more elements, and this is therefore preferred.

[0025] When the solid electrolyte of the present invention contains a plurality of elements as the X element, for example, X 1 Element and X 2 When two types of elements are included (preferably Li3YX 1 m X 2 n ), X 1 Element and X 2 The molar ratio of each element is, for example, X 1 It is preferable that the element is 30 mol % or more and 70 mol % or less, and X 2 The element is preferably present in an amount of 30 mol % or more and 70 mol % or less. The solid electrolyte of the present invention is X 1 element, X 2 Element and X 3 When the compound contains three elements (preferably Li3YX 1 m X 2 n X 3 k ), X 1 element, X 2 Element and X 3 The molar ratio of each element is, for example, X 1 The element is preferably 15 mol % or more and 50 mol % or less, and X 2 The element is preferably 15 mol % or more and 50 mol % or less, and X 3The content of the element is preferably 15 mol % or more and 50 mol % or less, in terms of increasing the degree of disorder.

[0026] From the viewpoint of increasing the degree of disorder, it is preferable that the solid electrolyte contains a plurality of elements as the X element, and at least one of the plurality of elements contains an I element, which is an element with a large ionic radius. In addition, when the solid electrolyte of the present invention contains an I element as the X element, there is also an advantage that the crystal system of the solid electrolyte is likely to be a monoclinic crystal. Achieving both high crystallinity and high degree of disorder contributes to improving lithium ion conductivity.

[0027] When the solid electrolyte of the present invention contains a plurality of X elements and contains at least an I element as the X element, examples of the combination of the X elements include a combination of a Cl element, a Br element, and an I element, and a combination of an F element, a Cl element, and an I element.

[0028] When the solid electrolyte of the present invention contains a plurality of elements as the X element, it is preferable from the viewpoint of improving lithium ion conductivity that the plurality of elements are present randomly in the crystal of the solid electrolyte, in other words, are not unevenly distributed.

[0029] Next, a preferred method for producing the solid electrolyte of the present invention will be described. In this method, the raw materials for the solid electrolyte are mixed, and the mixture is fired to produce the desired solid electrolyte.

[0030] In this production method, LiX (X is as defined above) and YCl3 are used as the compounds serving as raw materials for the solid electrolyte.

[0031] LiX, which is one of the raw materials, is generally in the form of powder. For example, LiI, LiF, LiCl, LiBr, etc. are used as LiX, and preferably at least two of these are used, and more preferably at least three of them are used. It is preferable to use at least LiI as LiX from the viewpoint of obtaining a solid electrolyte with high lithium ion conductivity.

[0032] The LiX powder preferably has an average particle size of, for example, 500 μm or less, particularly 300 μm or less, and especially 250 μm or less. With such a particle size, the raw materials of the solid electrolyte are easily mixed uniformly, and a solid electrolyte with high lithium ion conductivity can be produced. From this point of view, the smaller the average particle size of the LiX powder, the more desirable it is.

[0033] On the other hand, it is desirable that the average particle size of the YCl3 powder is, for example, 200 μm or less, particularly 150 μm or less, and especially 100 μm or less. With such a particle size, the raw materials of the solid electrolyte are easily mixed uniformly, and a solid electrolyte with high lithium ion conductivity can be produced. From this point of view, the smaller the average particle size of the YCl3 powder, the more desirable it is. In this specification, the term "average particle size" refers to the volume cumulative particle size D at 50% cumulative volume measured by a laser diffraction scattering particle size distribution measurement method. 50 This means that:

[0034] When LiX and YCl3 are mixed, the amounts of both used are preferably adjusted so that the target solid electrolyte has a composition of Li3YX6, from the viewpoint of producing a solid electrolyte with high lithium ion conductivity.

[0035] When mixing LiX and YCl3, it is preferable to mix them intensively from the viewpoint of producing a solid electrolyte with high lithium ion conductivity. For this purpose, it is preferable to adopt mechanical alloying for mixing LiX and YCl3. By adopting mechanical alloying, it is possible to perform very strong mechanical crushing and mixing, so that each element can be mixed uniformly at the atomic level.

[0036] Mechanical alloying can be carried out under known conditions. For example, LiX powder and YCl3 powder, the amounts of which are adjusted so that the composition of the target solid electrolyte is Li3YX6, are put into a ball mill, and pulverization and mixing are carried out. As the ball mill, a known device such as a planetary ball mill can be used. Mechanical alloying may be either a dry type or a wet type. In particular, dry type is preferable. The conditions of mechanical alloying can be appropriately set according to the properties of the powder raw material. In general, it is preferable to carry out the mechanical alloying at room temperature (particularly 0°C or higher and 50°C or lower) and at a rotation speed in the range of 100 rpm or higher and 500 rpm or lower. The atmosphere is preferably an inert gas atmosphere such as argon gas or nitrogen gas.

[0037] The mixture obtained by mechanical alloying is then subjected to a sintering process. The sintering is preferably performed at a temperature equal to or higher than the melting point of LiX. This allows LiX to melt during the sintering process, facilitating atomic diffusion, and making it easier to obtain a solid electrolyte with high crystallinity. In addition, when two or more types of LiX are used, atomic diffusion is more likely to occur, making the distribution of two or more types of X elements in the crystals random, making it easier to obtain a solid electrolyte with a large degree of disorder. As a result, it is easier to obtain a solid electrolyte with high lithium ion conductivity. The degree of crystallinity of the solid electrolyte obtained by the present production method can be evaluated by the intensity of the above-mentioned peak A. Specifically, it can be evaluated that the higher the intensity of peak A, the higher the crystallinity of the solid electrolyte.

[0038] In this specification, the "melting point of LiX" refers to the melting point of the LiX with the lowest melting point when two or more types of LiX are used.

[0039] The temperature S (°C) at which the mixture obtained by mechanical alloying is fired is preferably equal to or higher than the melting point of LiX as described above. When the melting point of LiX is M (°C), the firing temperature S is more preferably M≦S≦M+500, even more preferably M+50≦S≦M+400, and even more preferably M+100≦S≦M+300.

[0040] The firing time is preferably 4 hours or more, more preferably 6 hours or more, and even more preferably 8 hours or more, from the viewpoint of reliably obtaining a solid electrolyte with high crystallinity. Also, from the viewpoint of suppressing excessive volatilization of LiX, the firing time is, for example, preferably 30 hours or less, more preferably 25 hours or less, and even more preferably 20 hours or less.

[0041] The firing atmosphere is preferably an inert gas atmosphere such as argon gas, nitrogen gas, or the like.

[0042] After firing, the fired product may be crushed or pulverized as necessary, and may be classified as necessary. For example, it is preferable to crush or pulverize the fired product using a crusher such as a planetary ball mill, a vibration mill, or a tumbling mill, or a kneader.

[0043] The solid electrolyte thus obtained has a high degree of disorder and high crystallinity at the site where the X element is located, and has improved lithium ion conductivity. Therefore, the solid electrolyte of the present invention can be used as a material constituting a lithium battery, for example, a material constituting a solid electrolyte layer, a positive electrode layer, or a negative electrode layer.

[0044] Specifically, the solid electrolyte of the present invention can be used in a battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer. That is, the solid electrolyte can be used in a so-called solid-state battery. More specifically, the solid electrolyte can be used in a lithium solid-state battery. The lithium solid-state battery may be a primary battery or a secondary battery. There is no particular limitation on the shape of the battery, and for example, a laminate type, a cylindrical type, a square type, etc. can be adopted. The term "solid-state battery" includes a solid-state battery that does not contain any liquid or gel substance as an electrolyte, as well as an embodiment that contains, for example, 50% by mass or less, 30% by mass or less, or 10% by mass or less of a liquid or gel substance as an electrolyte.

[0045] When the solid electrolyte layer contains the solid electrolyte of the present invention, the solid electrolyte layer can be produced by, for example, a method of dropping a slurry consisting of a solid electrolyte, a binder, and a solvent onto a substrate and scraping it off with a doctor blade or the like, a method of contacting the substrate with the slurry and then cutting it with an air knife, a method of forming a coating film by a screen printing method or the like and then removing the solvent by heating and drying, etc. Alternatively, the solid electrolyte can also be produced by forming a powdered solid electrolyte into a compressed powder by pressing or the like and then appropriately processing it. From the viewpoint of the balance between short circuit prevention and volumetric capacity density, the thickness of the solid electrolyte layer is typically preferably 5 μm or more and 300 μm or less, and more preferably 10 μm or more and 100 μm or less.

[0046] The solid electrolyte of the present invention is used together with an active material to form an electrode mixture. The proportion of the solid electrolyte in the electrode mixture is typically 10% by mass or more and 50% by mass or less. The electrode mixture may contain other materials such as a conductive material as necessary. An electrode mixture, a binder, and a solvent are mixed to prepare a paste, which is then applied to a current collector such as aluminum foil and dried to prepare electrodes such as positive and negative electrodes.

[0047] As the positive electrode material constituting the positive electrode layer, a positive electrode material used as a positive electrode active material of a lithium ion battery can be appropriately used. For example, a positive electrode active material containing lithium, specifically, a spinel type lithium transition metal oxide and a lithium metal oxide having a layered structure, etc. can be mentioned. By using a high voltage positive electrode material as the positive electrode material, it is possible to improve the energy density. In addition to the positive electrode active material, the positive electrode material may contain a conductive material or other materials.

[0048] As the negative electrode material constituting the negative electrode layer, a negative electrode material used as a negative electrode active material in a lithium ion battery can be appropriately used. Since the solid electrolyte of the present invention is electrochemically stable, it can be used at a potential as low as lithium metal or a potential as low as lithium metal (about 0.1 V vs. Li + Carbonaceous materials such as graphite, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon), which are materials that are charged and discharged with a current of 0.1 W / Li, can be used as the negative electrode material. This can greatly improve the energy density of solid-state batteries. In addition, silicon or tin, which are promising high-capacity materials, can also be used as the active material. The negative electrode material may also contain a conductive material in addition to the negative electrode active material, or other materials. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0050] Example 1 (1) Preparation of raw materials LiCl powder (D 50 =200μm), LiBr powder (D 50 =215μm), LiI powder (D 50 = 55 μm) and YCl3 powder (D 50 = 35 μm) were weighed out. These powders were placed in a zirconia container and set in a planetary ball mill. Zirconia balls with a diameter of 10 mm were used as grinding media. The ball mill was operated at a rotation speed of 370 rpm, and dry mixing was carried out for 50 hours. The atmosphere was nitrogen. In this way, a mixture was obtained.

[0051] (2) Firing The mixture was fired to obtain a fired product. During firing, 100% pure nitrogen gas was circulated in the furnace. The firing temperature was raised to 550°C at 2°C / min and maintained at 550°C for 4 hours. In this manner, a solid electrolyte was obtained.

[0052] [Examples 2 and 3 and Comparative Examples 1 and 2] A solid electrolyte was obtained in the same manner as in Example 1 except that the conditions shown in Table 1 below were adopted.

[0053] 〔evaluation〕 X-ray diffraction measurements were performed under the following conditions for the solid electrolytes obtained in the Examples and Comparative Examples to determine the diffraction peak and half-width. Ion conductivity was also measured by the following method. The results are shown in Table 1 below. X-ray diffraction charts for the solid electrolytes obtained in the Examples and Comparative Examples are shown in FIG. 2.

[0054] [X-ray diffraction measurement] XRD measurements were performed using an X-ray diffraction device, "Smart Lab SE," manufactured by Rigaku Corporation. The measurement conditions were: no exposure to air, scanning axis: 2θ / θ, scanning range: 10° to 120°, step width: 0.02°, and scanning speed: 1° / min. The X-ray source was CuKα1 ray, the tube voltage was 40 kV, and the tube current was 80 mA.

[0055] [Ionic Conductivity] The solid electrolyte powders obtained in the examples and comparative examples were heated at about 6 t / cm in a glove box purged with sufficiently dried Ar gas (dew point -60°C or less). 2 A load of 10 ...

[0056] [Table 1]

[0057] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples exhibited higher ionic conductivity than the solid electrolytes of the comparative examples.

Claims

1. In the X-ray diffraction pattern using Cu-Kα1 as a radiation source, Peak A is in the range of diffraction angle 2θ of 13.4° or more and 14.4° or less, and Peak C is in the range of 30.7° or more and 33.7° or less, The sum of the half-widths of peak A is W A The sum of the half-widths of peaks C is W C Then, W C / W A A solid electrolyte having a value of 2.0 or more.

2. In the X-ray diffraction pattern using Cu-Kα1 as a radiation source, The diffraction angle 2θ has a peak D in the range of 43.8° or more and 48.8° or less, The sum of the half-widths of peaks D is W D Then, W D / W A The solid electrolyte according to claim 1, wherein the value of is 3.7 or more.

3. In the X-ray diffraction pattern using Cu-Kα1 as a radiation source, 3. The solid electrolyte according to claim 1, wherein the intensity of peak A is 25.0 or more in terms of relative intensity based on the intensity of the peak with the highest intensity among the observed peaks.

4. In the X-ray diffraction pattern using Cu-Kα1 as a radiation source, having a peak B in the range of a diffraction angle 2θ value of 26.2° or more and 29.2° or less; Peak D is in the range of 43.8° to 48.8°, Peak E in the range of 53.3° to 56.6°, The solid electrolyte according to claim 1 , having a peak F in the range of 55.9° or more and 59.0° or less.

5. 3. The solid electrolyte according to claim 1 or 2, comprising lithium (Li), yttrium (Y), and halogen (X) elements (X element represents one or more elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I).

6. The solid electrolyte according to claim 5 , wherein the X element includes at least iodine (I) element.

7. 6. The solid electrolyte according to claim 5, wherein the X element is two or more elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).

8. 6. The solid electrolyte according to claim 5, wherein the X element is three or more elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).

9. LiX (X represents a halogen element, and the X element is at least one selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I)), and YCl 3 and mixing the above by mechanical alloying. and firing the treated product obtained by mixing in an inert gas atmosphere at a temperature equal to or higher than the melting point of LiX.

10. The method according to claim 9, wherein the baking is carried out for 4 hours or more.

11. An electrode mixture comprising the solid electrolyte according to claim 1 and an active material.

12. A solid electrolyte layer comprising the solid electrolyte of claim 1.

13. 13. A battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, the solid electrolyte comprising the solid electrolyte of claim 1.

Citation Information

Patent Citations

  • Solid electrolyte material and battery

    WO2019135316A1

  • Solid electrolyte material and battery

    WO2019135319A1